Characterization of patients with recurrent ischaemic stroke using the ASCO classification. Issue 5 (8th January 2013) - Wolf, M. E.; Sauer, T.; Hennerici, M. G.; Chatzikonstantinou, A.
<x xml:space="preserve">Abstract</x> Background and purpose The ASCO score has the advantage of allowing a more comprehensive characterization of ischaemic stroke patients and their risk factors, as reflected in different grades of evidence of atherosclerotic changes (A), small vessel disease (S), potential cardiac (C) or other (O) sources. It might also help to characterize patients with recurrent ischaemic stroke and document the etiology of stroke recurrence as well as the further development of risk factor constellations. Methods We prospectively screened our stroke database for patients with recurrent ischaemic stroke between 2004 and 2011, and classified each stroke using ASCO. The distribution of etiologies was analysed, and changes in the ASCO score were documented for each patient. Results We identified 131 patients with recurrence of ischaemic stroke. At the first event, the distribution of etiologies and their grade of evidence was 97 grade 1 (A = 18/S = 32/C = 44/O = 3), six grade 2 (A = 2/S = 1/C = 3/O = 0), 199 grade 3 (A = 85/S = 83/C = 23/O = 8), 204 grade 0 (A = 26/S = 14/C = 44/O = 120) and 18 grade 9 (A = 0/S = 1/C = 17/O = 0). At stroke recurrence, 98 grade 1 (A = 16/S = 24/C = 55/O = 3), 11 grade 2 (A = 2/S = 5/C = 4/O = 0), 210 grade 3 (A = 94/S = 92/C = 13/O = 11), 171 grade 0 (A = 16/S = 9/C = 26/O = 117) and 34 grade 9 (A = 0/S = 1/C = 33/O = 0) were identified. Analysis of each individual showed a modification of the score in 85 patients (64.9%). Conclusions Recurrent ischaemic stroke does not always have the same etiology as the previous one(s). Among variable changes of grade 1 etiologies, an increasing prevalence of cardioembolism – often insufficiently treated – at stroke recurrence was a major finding. ASCO proved to be highly useful to monitor risk factor constellations.